Effect of non-alcoholic fatty liver disease on estimated glomerular filtration rate could be dependent on age - Shen, Zhe; Munker, Stefan (PLOS ONE, 2015)
There is a gap between the association of non-alcoholic fatty liver disease (NAFLD) and renal function in an apparently healthy population. This study aims to assess whether NAFLD is associated with estimated glomerular filtration rate (eGFR) levels and to understand early changes of eGFR in NAFLD. A cross-sectional study was performed among apparently healthy persons who underwent general health screening including laboratory assessments and hepatic ultrasonography from January 2013 to December 2013 at the First Affiliated Hospital of Zhejiang University, College of Medicine, China. This study included 1,193 subjects with a mean age of 48 years. Prevalence of NAFLD was 31.3%. Mean eGFR was significantly lower in NAFLD than in controls (107 ± 19 mL/min/1.73 m2 vs. 113 ± 23 mL/min/1.73 m2, P<0.001). Correlation analysis between eGFR and NAFLD related risk factors revealed an inverse correlation between eGFR levels and some NAFLD risk factors (all P<0.01). All subjects were classified into five phases according to age. Average eGFR levels of NAFLD were lower than controls in three phases for subjects with ≤ 50 years of age (all P<0.05), while there were no significant differences on average eGFR levels between NAFLD and controls in two phases for subjects with >50 years of age (Both P>0.05). The eGFR level is significantly associated with NAFLD and its risk factors in an apparently healthy population. Effects of NAFLD on eGFR could be dependent on age.